Role of hormonal levels on hospital mortality for male patients with severe traumatic brain injury. (September 2014) - Hohl, Alexandre; Ronsoni, Marcelo Fernando; Debona, Rodrigo; Ben, Juliana; Schwarzbold, Marcelo Liborio; Diaz, Alexandre Paim; Thais, Maria Emília Rodrigues de Oliveira; Linhares, Marcelo Neves; Latini, Alexandra; Prediger, Rui Daniel; Pizzol, Felipe Dal; Walz, Roger
Abstract Introduction: Changes in hormone blood levels during the acute phase of traumatic brain injury (TBI) have been described in the literature. The objective was to investigate the association among several hormones plasma levels in the acute phase of severe TBI and the hospital mortality rate of male patients. Methods: The independent association among plasma levels of TSH, LH, FSH, GH, free T4, cortisol, IGF-1 and total testosterone was measured 10 hours and 30 hours after severe TBI and the hospital mortality of 60 consecutive male patients was evaluated. Results: At least one hormonal level abnormality was demonstrated in 3.6–73.1% of patients. The multiple logistic regressions showed a trend for an independent association among hospital mortality and normal or elevated LH levels measured at 10 hours (OR = 3.7, 95% CI = 0.8–16.3, p = 0.08) and 30 hours (OR = 3.9, 95% CI = 0.9–16.7, p = 0.06). Admission with abnormal pupils and a lower Glasgow Coma Score also were independently associated with hospital mortality. Conclusion: The hormonal changes are frequent in the acute phase of severe TBI. The hormones plasma levels, excepting the LH, are not highly consistent with the hospital mortality of male patients.